2010
DOI: 10.3340/jkns.2010.48.4.375
|View full text |Cite
|
Sign up to set email alerts
|

Chiari 1.5 Malformation : An Advanced Form of Chiari I Malformation

Abstract: J Korean Neurosurg Soc 48 : [375][376][377][378][379] 2010 The Chiari 1.5 malformation is defined as a tonsillar herniation within a Chiari I malformation with additional caudal descent of the brainstem through the foramen magnum. We describe a patient with Chiari I malformation who evolved to Chiari 1.5 malformation during longitudinal follow-up. A 15-year-old girl presented with neck pain during exercise for two years. She had been diagnosed with Chiari I malformation with mild hydrocephalus after minor c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 14 publications
2
36
0
Order By: Relevance
“…16 The 8-mm mean distance of the obex from the FM in our patient cohort was less than the 10-to 12-mm distance observed in healthy populations. 24,29 This suggests that, along with the classic tonsillar descent in CMI, the cervicomedullary junction also tends to be caudally displaced toward the FM.…”
Section: Correlations Of Preoperative Radiological Variables With CMImentioning
confidence: 89%
“…16 The 8-mm mean distance of the obex from the FM in our patient cohort was less than the 10-to 12-mm distance observed in healthy populations. 24,29 This suggests that, along with the classic tonsillar descent in CMI, the cervicomedullary junction also tends to be caudally displaced toward the FM.…”
Section: Correlations Of Preoperative Radiological Variables With CMImentioning
confidence: 89%
“…CMI along with brainstem herniation is also referred to Chiari malformation type 1.5 (CM 1.5) (14,30). It is reported that there is no specific sign or symptom peculiar to CM 1.5, but the incidence of unresolved SM after SPFD is nearly two-fold higher in CM 1.5 than CMI.…”
Section: Risk Factors On Prognosismentioning
confidence: 98%
“…In 1998, Iskandar et al (12) described 'Chiari Zero malformation' to characterize a type of syringomyelia that exhibits classical CM-1 symptoms with little to no herniation. In 2010, Kim et al described 'Chiari 1.5 malformation' as an advanced form of CM-1 (14).…”
Section: Introductionmentioning
confidence: 99%